2017
DOI: 10.1117/1.jmm.16.3.034504
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of resonator-quantum well infrared photodetector for SF6 gas sensor application

Abstract: Abstract. The infrared absorption of SF 6 gas is narrowband and peaks at 10.6 μm. This narrowband absorption posts a stringent requirement on the corresponding sensors as they need to collect enough signal from this limited spectral bandwidth to maintain a high sensitivity. Resonator-quantum well infrared photodetectors (R-QWIPs) are the next generation of QWIP detectors that use resonances to increase the quantum efficiency for more efficient signal collection. Since the resonant approach is applicable to nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…QWIPs made of other materials (e.g., InGaAs/InP) 40 have shown similar or higher responsivity and detectivity; SWAs can be combined with these materials as well. Through these optimizations, less toxic SWA-enhanced QWIPs would replace the widely used but toxic HgCdTe detectors 26 in some spectroscopic applications [15][16][17][18] . As Palaferri et al demonstrated 12 , gigahertz-frequency detection would be another promising application that only antenna-enhanced QWIPs can realize.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QWIPs made of other materials (e.g., InGaAs/InP) 40 have shown similar or higher responsivity and detectivity; SWAs can be combined with these materials as well. Through these optimizations, less toxic SWA-enhanced QWIPs would replace the widely used but toxic HgCdTe detectors 26 in some spectroscopic applications [15][16][17][18] . As Palaferri et al demonstrated 12 , gigahertz-frequency detection would be another promising application that only antenna-enhanced QWIPs can realize.…”
Section: Discussionmentioning
confidence: 99%
“…In this Article, we not only clarify the physical foundations underlying the SWAs, but also present their application to mid-infrared photodetectors incorporating only a single quantum well (QW). Practical responsivity without polarization dependence at a predetermined wavelength in the fingerprint region, extending up to room temperature, is promising for spectroscopic applications [15][16][17][18] and free-space data transfer 12 . However, applications are not limited to detectors; SWAs offer greater design freedom as a fundamental platform for optoelectronic metadevices [19][20][21] .…”
mentioning
confidence: 99%
“…However, the quantum efficiency of quantum well detectors has always been a difficult problem to overcome. In order to solve this problem, many teams have conducted corresponding research work [1][2][3][4][5][6][7] . Among them, the Arnaud Berurier team has conducted research on 11-14um wide spectral detectors [8] .…”
Section: Introductionmentioning
confidence: 99%